Predicting individuals’ behaviors during a pandemic: why we might have acted as we did during the COVID-19 pandemic - Shaikha S. Aldousari; William Ickes (Current Issues in Personality Psychology)
Background This study examined individual differences in how people behave in response to a pandemic – more specifically, the current coronavirus pandemic.